Fearless leadership : overcoming reticence, procrastination, and the voices of doubt inside your head - Weiss, Alan, 1946- (New York : Routledge, 2020)
"The intent of this book -- the author's goal for you - is to understand the baseless underpinnings of almost all our fears. You read that correctly -- almost all our fears -- and therefore to discard them. The author has expertly coached leaders and managers in the discovery of, examination of, elimination of, and sustained freedom from fears. We all know people who are charming and articulate, but flounder on a stage addressing colleagues; musicians who master intricate scores but can't play the basics when asked to solo; athletes who "choke"; business people who are strong until it comes time to ask for the business; people who consistently feel like "imposters." We are far better at dealing with external, tangible fears than our own imagined ones. We purchase insurance, watch the safety demonstrations, know how to use the Heimlich Maneuver. But those are responses to rare and often never-occurring emergencies. Our mythical and monstrous fears are daily dark clouds, masking our talents no less than depression or guilt. It's time to realize there is no monster under the bed, never has been, and never will be without having to check nightly and without needing a weapon on the night table. Picture yourself freed of restraints that you could never properly articulate and were loath to discuss, but which you carried on your shoulders constantly, a dead weight, nonetheless. Essentially, this book is for entrepreneurs, business owners, and those who seek a better position for themselves and their talents, but who procrastinate, delay, and hang back. It's about isolating and overcoming the internal fears that we generate every day like a geyser, triggered by time, events, or shifts in the environment. We are our own worst enemies and we ignore the practical remedies to escape fear because we use our energies instead on blaming everyone else"--
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Motivational